Competency Costs in Foreign Affairs: Presidential Performance in International Conflicts and Domestic Legislative Success, 1953–2001. Issue 2 (16th December 2014) - Gelpi, Christopher; Grieco, Joseph M.
<x xml:space="preserve">Abstract</x> Numerous prominent theories have relied on the concept of "audience costs" as a central causal mechanism in their arguments about international conflict, but scholars have had greater difficulty in demonstrating the efficacy and even the existence of such costs outside the bounds of game theory and the political psychology laboratory. We suggest that the audience costs argument focuses too narrowly on the likelihood that leaders will be removed from office by domestic constituencies for failing to make good on threats. Instead, we argue that scholars should ground these arguments on Alastair Smith's (1998) broader concept of "competency costs." Our analysis of presidential legislative success from 1953 to 2001 demonstrates the existence of foreign policy competency costs by showing that public disapproval of presidential handling of militarized interstate disputes has a significant and substantial negative impact on the president's ability to move legislation on domestic issues through Congress.